Enoxaparin-Induced Liver Injury: Case Report and Review of the Literature and FDA Adverse Event Reporting System (FAERS) - Hahn, Katherine J.; Morales, Shannon J.; Lewis, James H. (Drug safety - case reports, 2015)
Anticoagulants are a well known cause of drug-induced liver injury (DILI). We recently encountered a 45-year-old male who developed DILI during treatment with enoxaparin, a low-molecular-weight heparin (LMWH), for dural venous thrombosis. The man received enoxaparin 80 mg subcutaneously, twice daily. After 4 days, the patient was asymptomatic but he developed liver aminotransferase elevations: AST 340 U/L and ALT 579 U/L. Investigation revealed an R ratio of 19.9 by day 5 and a Roussel Uclaf Causality Assessment Method score of 10, giving a high probable likelihood that enoxaparin was the cause of hepatic injury. Enoxaparin was discontinued on day 7, and 1 week later AST and ALT had decreased to 61 and 273 U/L, respectively. This case prompted a literature search and a review of the FDA Adverse Event Reporting System (FAERS) database for the range of hepatic adverse events (HAEs) associated with this class. A MEDLINE/PubMed search was conducted using DILI terms and cross-referenced with the anticoagulant classes. A Freedom of Information Act (FOIA) request was also made to identify adverse events (AEs) associated with enoxaparin in FAERS. Case type, severity of outcome, and demographic information were analyzed. Five publications have reported DILI with enoxaparin. Trial data found elevations in ALT >3 times the upper limit of normal (ULN) for unfractionated heparins (UFH) and LMWH in 8 and 4–13 % of subjects, respectively. However, liver injury in all cases was mild, self-limited, and asymptomatic. Our FOIA request yielded 8336 adverse events related to enoxaparin over a 14-year period (Jan 2000–Sept 2014). Specific HAEs were found in 4 % of reports, but all were described with other serious adverse events. The reported outcomes of hospitalization (75 %), death (17 %), and life-threatening medical events (5 %) were likely due to other related serious adverse events such as hemorrhage (28 %) and thrombocytopenia (11 %). We conclude that LMWH-related liver injury is uncommon and reversible. The mechanism of liver injury is not known, although an idiosyncratic effect is postulated. Although the FAERS database lists hepatic injury in 4 % of all enoxaparin-related AEs, it appears that serious outcomes are related to non-hepatic events.